2022
DOI: 10.1075/wlp.10
|View full text |Cite
|
Sign up to set email alerts
|

Esperanto – Lingua Franca and Language Community

Abstract: As its title suggests, this book is concerned with the use of Esperanto. In our experience, very few people know that this language really is used, in both writing and speech, and that it has found speakers all over the world. To a certain extent, even to us, it is sometimes hard to imagine that a language created by a single person at his desk has developed for more than a hundred and thirty years to become a fully fledged means of communication. It is our wish to provide insights into as many fields and ways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 238 publications
0
0
0
Order By: Relevance
“…This required the participants to use English frequently in written and spoken communication with diverse communities. This strengthens other ELF studies which found that ELF settings would boost L2 confidence because cooperative strategies, negotiated meaning, and non-standard native form were commonly used in a conversation among ELF users (Fiedler, 2011;Kalocsai, 2011;Kaur, 2011;Ke & Cahyani, 2014;Lazaretnaya, 2012;Seidlhofer, 2005).…”
Section: Compromising the Belief In Ns Normssupporting
confidence: 83%
See 1 more Smart Citation
“…This required the participants to use English frequently in written and spoken communication with diverse communities. This strengthens other ELF studies which found that ELF settings would boost L2 confidence because cooperative strategies, negotiated meaning, and non-standard native form were commonly used in a conversation among ELF users (Fiedler, 2011;Kalocsai, 2011;Kaur, 2011;Ke & Cahyani, 2014;Lazaretnaya, 2012;Seidlhofer, 2005).…”
Section: Compromising the Belief In Ns Normssupporting
confidence: 83%
“…Unlike the prior research, this study investigated L2 confidence in ELF settings. Since many studies revealed that ELF users commonly deployed cooperative strategies (Fiedler, 2011;Kalocsai, 2011;Kaur, 2011;Ke & Cahyani, 2014;Lazaretnaya, 2012;Seilhamer, 2015), negotiated meaning and tended to apply non-standard native form, ELF environments might have both positive and negative influences on the dynamic process of L2 English confidence development.…”
Section: L2 Confidence and Elfmentioning
confidence: 99%
“…In general, students were moderately motivated to take the course to become a Math teacher in English, while Loima and Vibulphol (2016) found contradicting findings in the regional study that a high level of motivation was found among Thai students. This relatively high degree of enthusiasm to learn English has been seen in other EFL situations as well (Cho, 2012;Winewska, 2013), which supports the idea that English is a necessary skill for individuals all over the world (Fiedler, 2011;Johnson, 2009). The reason for this is that the samples in this study are Vietnamese, while in Wong's study (2011), the samples are primarily Chinese students.…”
Section: Survey Questionnaire Partsupporting
confidence: 60%
“…Language attitude has become a focus of attention for sociolinguists and social psychologists over the last few decades. Not only is language considered a communicative device conveying information, but it also psychologically constructs and defines individual identities and social characteristics of the speakers, whether through their own language or the languages of others (Coupland, 2007;Edwards, 1999;Fiedler, 2011;Jenkins, 2007;Kim, 2012;Ladegaard, 1998Ladegaard, , 2000Rindal, 2010;Sung, 2014).…”
Section: Language Attitudementioning
confidence: 99%